1H-NMR analysis of degree of substitution in N,O-carboxymethyl chitosans from various chitosan sources and types - A. Jaidee (2018)
N, O-Carboxymethyl chitosans were synthesized by the reaction between shrimp, crab and squid chitosans with monochloroacetic acid under basic conditions at 50°C. The mole ratio of reactants was obtained from various reaction conditions of shrimp chitosan polymer and oligomer types. The mole ratio 1:12:6 of chitosan:sodium hydroxide:monochloroacetic acid was used for preparing carboxymethyl of chitosan polymer types while carboxymethyl of chitosan oligomer types were used the mole ratio 1:6:3 of chitosan:sodium hydroxide:monochloroacetic acid. The chemical structure was analyzed by fourier transformed infrared spectroscopy (FT-IR) and proton nuclear magnatic resonance spectroscopy ( 1H-NMR). The FT-IR was used for confirm the insertion of carboxymethyl group on chitosan molecules. The 1H-NMR was used for determining the degree of substitution (DS) of carboxymethylation at hydroxyl and amino sites of chitosans. Carboxymethyl chitosan samples had the total DS of carboxymethylation ranging from 1.0-2.2. The highest of DS of carboxymethylation was from shrimp chitosan oligomer type. © (2012) Trans Tech Publications.